HALAL AWARENESS AND HALAL TRACEABILITY: MUSLIM CONSUMERS’ AND ENTREPRENEURS’ PERSPECTIVES - Syayyidah M. Jannah; Hasan Al-Banna (Bank Indonesia, 2021)
The objective of this paper is to analyse the role of halal awareness, employing variables that can be both influential (determinant) and influenced (output). The study examines two perspectives, namely those from consumers and business actors. From a consumer perspective, this relates to the influence of halal awareness on the intention to purchase a halal product. Meanwhile, from the perspective of business actors, it considers how halal awareness affects the halal traceability of products. Halal traceability is also analysed from the consumers’ perspective as a moderating variable in the relationship between halal awareness and consumer purchase intentions. Questionnaires were distributed online and data were collected from 176 consumers and 95 entrepreneurs. SEM-PLS was then applied to analyse the data. The results show that halal awareness influences the consumers’ purchase intention and the halal traceability of the business actors. While the consumers’ halal awareness was determined by knowledge and halal certification. In contrast, religiosity has an insignificant influence on the consumers’ halal awareness. Meanwhile, the halal awareness of the business actors was influenced by knowledge, halal certification and religiosity. Halal traceability failed to moderate the relationship between halal awareness and consumer purchase intentions.